“Like, we can’t keep adding”: a mixed methods study to explore the feasibility of implementing co-produced 24-Hour Movement Guideline content - Morgan, Tamara L; Nowlan Suart, Theresa; Fortier, Michelle S; Kelman McFadyen, Isaac; Tomasone, Jennifer (Canadian Medical Education Journal, 2024)
Background: Medical students must demonstrate competency in health promotion and illness prevention; however, movement behaviour promotion content is lacking in medical curricula. Canada’s 24-Hour Movement Guidelines (24HMG) present an opportunity to transform medical curricula to promote movement behaviours within a 24-hour paradigm. We previously co-produced a 24HMG curriculum map and 14 curriculum objectives at one Canadian medical school. The aim of this study was to gain consensus on the curriculum map and objectives among faculty and medical students and explore implementation determinants. Methods: This study followed a concurrent nested mixed methods design using a modified Delphi method to assess the level of (dis)agreement with map components followed by interviews to explore the implementability of the map. A preliminary survey was distributed to collect demographic and movement behaviour data, followed by three online modified Delphi surveys. Suggested improvements to the map were solicited through open-text boxes. Interviews were semi-structured and conducted online. Interview data were analyzed using content analysis guided by the Consolidated Framework for Implementation Research (CFIR) 2.0. Results: Consensus was reached on 156/180 items (86.7%) in Survey 1 (faculty, n = 6; students, n = 8), 49/51 items (96.1%) in Survey 2 (faculty, n = 4; students, n = 7), and 8/8 items (100%) in Survey 3 (faculty, n = 3; students, n = 7). Implementation determinants encompassed all five CFIR 2.0 domains, mostly the inner setting (e.g., culture, structural barriers). Conclusions: Reciprocity and open communication between medical schools and external change agents should be prioritized when co-producing curriculum change in the present landscape of inflation and medical professional burnout.